Aedestech Mosquito Home System prevents the hatch of Aedes mosquito eggs and reduces its population - Saiful Yazan, Latifah; Paskaran, Kaveinesh; Gopalsamy, Banulata; Abd. Majid, Roslaini (Universiti Putra Malaysia Press, 2020)
Dengue fever (DF) is a global health problem and considered to be endemic in Malaysia. Conventional mosquito traps currently applied as vector control do not effectively reduce Aedes mosquito population. AedesTech Mosquito Home System (AMHS) is an autocidal ovitraps for Aedes mosquitoes that uses the ‘lure and kill’ concept and is expected to be able to reduce Aedes mosquito population. The effectiveness of AMHS in reducing Aedes mosquito population was investigated in Block A, B and D (control) of the 17th College, Universiti Putra Malaysia (UPM). For the first two weeks (pre-intervention), the conventional ovitraps were used to obtain the initial abundance of mosquito population in Block A, B and D. Subsequently, AMHS was used for the next three months and again followed by the conventional ovitrap for the final two weeks (post-intervention). Ovitrap Index, Hatching Index and percentage of emergence of adult mosquitoes were calculated once every two weeks. Data were analysed using Paired Sample T-test. Values were considered significant at p≤0.05. The Ovitrap Index that indicates the mosquito population at Block A and B was significantly higher (p≤0.05) than of Block D. Hatching Index of AMHS was significantly lower (p≤0.05) then conventional ovitraps. All mosquito eggs collected in AMHS did not develop into adult mosquitoes. There was a significant reduction (p≤0.05) in the mosquito population between the pre- and post-intervention. In conclusion, AMHS was effective in reducing the mosquito population in 17th College, UPM. Therefore, it is believed to be a very promising vector management option to control the incidence of DF.